2014
DOI: 10.1039/c4ra08682a
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and application of a diazirine-modified uridine analogue for investigating RNA–protein interactions

Abstract: A uridine analogue equipped with a photoactive diazirine unit was generated and incorporated into RNA either syntheticallyviaphosphoramidite chemistry or by enzymatic polymerization. The new analogue was developed to identify and investigate RNA–protein interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 101 publications
2
18
0
Order By: Relevance
“…6‐Iodouridine was reported as a potent inhibitor of the malaria parasite . Nucleoside derivatives are also applied in molecular probes , fluorescent surrogates , duplex stabilizing component , glucose uptake , anti‐epileptic, and identification of RNA binding proteins . Furthermore, many nucleoside analogues possessing antiviral and antitumor activities are already used clinically.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6‐Iodouridine was reported as a potent inhibitor of the malaria parasite . Nucleoside derivatives are also applied in molecular probes , fluorescent surrogates , duplex stabilizing component , glucose uptake , anti‐epileptic, and identification of RNA binding proteins . Furthermore, many nucleoside analogues possessing antiviral and antitumor activities are already used clinically.…”
Section: Methodsmentioning
confidence: 99%
“…or acyl chloride (4 equiv.) to get acyl oleanolic acid compounds (9)(10)(11)(12)(13)(14) at moderate yields of 61-89%. These acyl oleanolic acid 9-14 (1 equiv.)…”
Section: Synthesismentioning
confidence: 99%
“…In this sense, tC O TP behaves better or on par with a majority of previously modified nucleotides, 35,36,[55][56][57] including bulkier triphosphate analogues. 58,59 It has been reported that the T7 RNA polymerase binds the incoming nucleotide substrate in an open conformation, 60 which could enable it to accommodate our modified base. Cell-free enzymatic incorporation of tC O into mRNA transcript…”
Section: Cell-free Enzymatic Incorporation Of Tc O Into Rnamentioning
confidence: 99%
“…Aryl ketones, aryl azides and diazirines are the most popular photoreactive groups used for the photo cross-linking 30 , 31 . In fact, these have been used to study the cross-linking of DNA-DNA 32 or protein-DNA/RNA complexes 33 36 , to probe protein-protein interactions 37 , 38 or to attach a variety of biomolecules to polymer surfaces 39 , 40 . In addition, novel click chemistry-based photo-crosslinkers (e.g., tetrazole) have proved to be very promising as alternative photo-labels 41 .…”
Section: Introductionmentioning
confidence: 99%